A percepção do sistema agroindustrial avícola brasileiro em relação as barreiras verdes no comércio internacional - Flores, Rafael Telch (2023)
This study aims to identify the perception of the Brazilian Agroindustrial Poultry System concerning the impacts caused by environmental issues in the sector. The study presents the main challenges that will be imposed on the national poultry industry by means of the international standardization of agro-industrial systems, as well as an analysis of the eco-protectionism phenomenon and the green barriers that will be imposed on the sector. The methodology used was the Delphi technique, through the application of questionnaires to specialists who work in the Brazilian poultry sector. The data treatment was done by means of structural analysis of the variables using the MICMAC software. Through the results obtained it is possible to conclude that the Brazilian poultry agribusiness system has an understanding of the adversities, but the measures necessary to mitigate the impacts have not yet been assigned as a central activity by the Federal Government and especially by the market.